Please help, will give brainliest answer
Please help, will give brainliest answer - 1

Answers

Answer 1
Answer:

I do khan academy 2 but sorry the answer


Related Questions

What numbers multiply to -35 and add up to -2?
Let f(x,y)=x^2 + ln(y).Calculate the instantaneous rate of change at (3,1) to (1,2).
Someone help me PLZZ
Kayla pays her plumber $22 per hour to replace her drain pipe. She ends up paying him $99. Which equation can you use to find h, the number of hours the plumber worked?
A certain alloy contains 14.25% nickel. how much nickel is there in a piece weighing 375 pounds? round to the nearest hundredth.A.112.49B.78.92C.12.24D.5344

What is 45% of 40 in part, whole, and percent?

Answers

The answer is eighteen.

CAN SOMEONE PLEASE HELP ME I NEED HELP

Answers

Answer:

4^2

Step-by-step explanation:2*2

The sum of two consecutive integers is 59. Write an equation that models this situation and find the values of the two integers.A.) n+n+1=59;n=30;n+1=31
B.) n+2n=59;n=19;2n=38
C.) n+n+1=59;n=29;n+1=28
D.) n+n+1=59;n=29;n+1=30

Answers

An equation that models this situation: n + n +1 = 59 ( two consecutive integers: n, n+1 and their sum is 59)
2 n+1 = 59
2 n = 58
n = 58 : 2
n = 29,   n + 1 = 30
Answer:D) n + n + 1 = 59,  n = 29, n + 1 = 30

Answer:

D) n + n + 1 = 59,  n = 29, n + 1 = 30

Step-by-step explanation:

F(x) = x + 4: find f(4) and f(x) = 10

Answers

Answer:

f(4) = 8

f(6) = 10

Step-by-step explanation:

Step 1: Define

f(x) = x + 4

f(4) is x = 4

f(x) = 10

Step 2: Find f(4)

f(4) = 4 + 4

f(4) = 8

Step 3: Find f(x) = 10

10 = x + 4

x = 6

Suppose a triangle has sides 3 4 and 5, which of the following must be true

Answers

You haven't given any options to select. 
However, if this is the way of values we can check pythagoras theorem .

5^2 = 25

3^2 + 4^2
9 + 16
25

25 = 25

therefore we can say it is the right angle triangle

Consider a situation in which P(X) = and P(Y) = . If P(X and Y) is = , which best describes the events?They are independent because P(X) · P(Y) = P(X and Y).
They are independent because P(X) + P(Y) = P(X and Y).
They are dependent because P(X) · P(Y) = P(X and Y).
They are dependent because P(X) + P(Y) = P(X and Y).

Answers

Answer:

They are independent because P(X) · P(Y) = P(X and Y).

Step-by-step explanation:

Two events are independent if the occurrence of one event does not affect the probability of the occurrence of the other event. This means that the probability of both events happening is equal to the product of the probabilities of each event happening individually.

In the given situation, we have:

P(X) = 1/2

P(Y) = 1/2

P(X and Y) = 1/4

If we calculate the product of P(X) and P(Y), we get:

P(X) · P(Y) = 1/2 · 1/2 = 1/4

This is equal to P(X and Y), which means that the events X and Y are independent.

P(X) + P(Y) = P(X and Y) is not a necessary condition for independence. For example, the events of flipping a coin and rolling a die are independent, but P(X) + P(Y) ≠ P(X and Y).

Therefore, the best description of the events is that they are independent because P(X) · P(Y) = P(X and Y).